Long-term studies on the integration of acellular porcine dermis as an implant shell and the effect on capsular fibrosis around silicone implants in a rat model - Ludolph, I.; Grüner, Johanna; Kengelbach-Weigand, Annika; Fießler, Cornelia; Horch, Raymund E.; Schmitz, Marweh (Journal of Plastic Reconstructive and Aesthetic Surgery, 2019)
Acellular dermal matrices have recently increasingly been used in alloplastic breast reconstruction with silicone breast implants. Among these matrices, acellular porcine dermis (APD) is frequently applied, but long-term data on tissue integration and capsular fibrosis formation are still missing. Silicone prostheses with (group A) and without (group B) APD as an implant-covering shell were implanted in male Lewis rats. At 3, 12, and 52 weeks after implantation, the constructs were explanted. Molecular biological and immunohistochemical analyses were performed afterwards. On comparing the collagenous layer and the newly formed myofibroblast-rich layer around the implants of both groups, it became apparent that in group A, these layers were thinner, followed by a lower expression of TGFβ1 after 12 and 52 weeks. Further, in this group, at the endpoint of 52 weeks, a lower amount of CD68-positive cells in the collagenous and myofibroblast-rich layers were observed and the expression of TNFα was reduced, while the number of Ki67-positive cells was significantly higher with time. Furthermore, MMP1 expression in group A was lower than that in group B, and the calculated ratio of MMP1:TIMP1 expression was higher. The long-term results clearly show a reduction in inflammatory and fibrotic tissue reaction when APD is used to cover silicone prostheses. These experimental data will be of considerable importance for implant-based breast surgery, as they indicate a potential benefit in the reduction of capsular fibrosis formation of an interposition of APD between the recipient and the silicone implant.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Acellular porcine; Breast reconstruction; Capsular contracture; Capsular fibrosis; Dermal matrix